2023
DOI: 10.3390/nu15081896
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals in Cancer Treatment and Cancer Prevention—Review on Epidemiological Data and Clinical Trials

Abstract: Phytochemicals are a non-nutritive substances that are present in plants and contribute significantly to their flavor and color. These biologically active compounds are classified into five major groups, namely phenolics, carotenoids, organosulfur compounds, nitrogen-containing compounds, and alkaloids, and are known for their potential health benefits in the prevention of various diseases, including cancer. The purpose of this review article is to explore the potential therapeutic benefits of the dietary phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 205 publications
0
19
0
Order By: Relevance
“…Natural products are a valuable resource for new drug candidates over the past few decades [ 38 ]. Phytochemicals, including flavonoids, stilbenes, terpenoids, and alkaloids, have been widely explored for their potential in cancer prevention and treatment [ 39 ]. More recent studies have revealed the ability of plant extracts or compounds to suppress the stem-like properties of cancer cells [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural products are a valuable resource for new drug candidates over the past few decades [ 38 ]. Phytochemicals, including flavonoids, stilbenes, terpenoids, and alkaloids, have been widely explored for their potential in cancer prevention and treatment [ 39 ]. More recent studies have revealed the ability of plant extracts or compounds to suppress the stem-like properties of cancer cells [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sublethal damage caused by the anticancer drug(s) to normal cells leads to rapid cell division as well as frequent toxicity to the organs of patients. Based on epidemiological data, the daily consumption of natural polyphenolic compounds can lower the risk of heart disease as well as the prevalence of various cancer types [24,25].…”
Section: Cases Of Anticancer Activity In Prostate Cancermentioning
confidence: 99%
“…However, cancer treatments have mostly relied on specific cytotoxic chemotherapy, and their impact on dividing healthy cells results in adverse side effects. There is a renewed interest in natural compounds that can inhibit the growth and metastasis of cancer, and investigations of their adjuvant effects with traditional chemo-drugs are underway [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%